Electroacupuncture on Hemifacial Spasm and Temporomandibular Joint Pain Co-Morbidity: A Case Report - Huang, Jian-peng; Liang, Zhan-mou; Zou, Qi-wen; Zhan, Jie; Li, Wen-ting; Li, Sheng; Li, Kai; Fu, Wen-bin; Liu, Jian-hua (Frontiers in Neurology, 2022)
Hemifacial spasm (HFS) and temporomandibular joint (TMJ) pain are common facial diseases which cause depression, anxiety, insomnia, and poor quality of life. However, currently there are still no effective therapies to treat HFS and TMJ. Electroacupuncture (EA) has advantages of safety, rapid work, easy operation and convenience. Here, we reported a case of a 50-year-old woman who presented with irregular spasm of eyelids and facial muscles on the left side, and TMJ pain on the right side. The patient had been treated with carbamazepine (20mg per day) and alternative therapies for a year, but still not much improvement in the symptoms. The scores of the Jankovic Rating Scale (JRS), global rating scale (GRS), and visual analog scale (VAS) were 7, 60, and 7 points, respectively. The EMG test showed that the spastic side had higher R1 amplitude, longer R2 duration, and larger R2 area than the non-spasmodic side, and the occurrence rate of the lateral spread responses (LSR) in the Orbicularis oris and the Orbicularis oculi muscle was 60% and 40%, respectively. We considered this patient had left HFS and right TMJ pain. EA was successfully undertaken for two periods over 30 weeks. After EA, JRS and VAS were reduced sharply, and the symptoms of HFS were stable without recurrence. However, the frequency of the lower eyelid increased gradually during the 6-month follow-up. These findings reveal that EA with the frequency of 2 Hz and intensity of ~ 1–2 mA may be a benefit for alleviating symptoms of HFS and TMJ pain without adverse reaction. The potential mechanisms of EA in HFS and TMJ pain co-morbidity involve brain stem mechanism and DNIC mechanism for distal acupuncture and segmental mechanism for local acupuncture analgesia.